Islamic Literature and Al-Iltizam (Commitment) in the Short Story “Al-Kabus” from the Anthology Al-Kabus wa Qasas Ukhra by Najib Al-Kailani - Pratiwi, Dian Rizki; Rahim, Rahmawati Anisa (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2026)
Arabic literature has developed since the Jahiliyah period and continued until the emergence of Islam. Then, Islamic literature was born which played an important role in conveying Islamic values ​​and teachings. This study discusses one of the concepts in Islamic literature initiated by Najib al-Kailani in his book Madkhal Ila al-Adab al-Islami, namely al-Iltizam (Commitment). The purpose of this study is to reveal how Najib al-Kailani, a figure who initiated the concept of al-Iltizam in Islamic literature, applies his own concept in building stories, characters, and messages conveyed in his work in the form of a short story entitled “al-Kabus”. This study is a library research with a qualitative descriptive type, which focuses on the analysis of narratives in the literary work. The results of this study indicate that the concept of Al-Iltizam or commitment in Islamic literature has a very important role in forming literary works that are not only aesthetic but also meaningful, and contain Islamic teachings and values ​​in them. Thus, al iltizam in Islamic literature can be a powerful means to spread moral and spiritual messages, as well as to shape the character of a better society.